Kepastian Hukum Pembatalan Akta Notariil Menjadi Akta di Bawah Tangan Pada Perjanjian Kerjasama - Arya Putra Rizal Pratama; Moch.Takim; Rifkah Romizah (Riau Law Journal, 2022)
Wiralogam Company with Citi9 Property Indonesia made an Operational Cooperation Agreement (KSO) for the development of the Tenaru 9 Project. Where in this agreement Wiralogam Company made a loan of IDR. 12.000.000.000,00 (two billion rupiah) to Citi9 Property Company Indonesia through the Notarial Deed of Agreement. However, there was a legal dispute where the owner of Wiralogam without the knowledge of the occurrence of retroactive notarial deed becomes under the hand. This resulted in alleged losses in which Wiralogam Company borrowed money with collateral in the form of land and shop houses covering an area of 20,450m2 (square) and it was as if the cancellation of the cooperation agreement was under the pretext of PT. Wiralogam failed to repay the debt based on what was agreed. This study uses legal research methodswitha statutory approach (status approach), conceptual approach (conceptual approach), and case approach (case approach). The results of this study explain that the application of the agreement under the hands and the date back without the knowledge of Wiralogam Company is an unlawful act on a contract which is contrary to the freedom to contract based on good faith as regulated in Article 1338 paragraph (3) BW. However, the legal protection that must be carried out by PT. Wiralogam as the aggrieved party is to unilaterally cancel through the court on the basis of fundamental losses. Therefore, after the cancellation, a lawsuit against the law must be carried out on the contract as well as abuse of circumstances based on defects of will and deception on the basis of Article 1321 BW